WATERSHED TOPOGRAPHIC CHARACTERISTICS AND CAUSES ANALYSIS OF THE UPPER REACHES OF THE WEIHE RIVER - Z. H. Liu; L. Han; L. Han; T. T. Wu; C. Y. Du; N. Cao (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
The morphology of watershed is the most intuitive information carrier to reflect regional tectonic activity, surface erosion and morphologic evolution. Active tectonic and fluvial system play a significant role in patterns and characters of regional morphology. Taking twenty-nine tributaries of the upper reaches of the Weihe River as the main study objects, four parameters, such as gully density (GD), basin topography ratio (BTR), roundness ratio (RR), river longitudinal profile fitting exponent (RLPFE), etc., were used to quantitatively analyse the topographic characteristics in this area. To reveal the main cause of the characteristics, the hypsometric integral (HI) were also applied in this area. The results showed that: (1) There is a positive linear function between basin topography ratio (BTR) and mean slope, and the mean values of four indexes in northern channels are smaller than southern channels; (2) The mean HI value is 0.44, indicating that the main topographic characteristics of this area is in maturity, which is in the transitional period of adjustment of the deep erosion and uplift movement; (3) The main cause of this topographic changes is tectonic. These results are consistent with other geological background, and will enrich regional basin morphology research and tectonic activity evaluation, provide important basic data for regional disaster prediction and analysis of soil and water loss.